The behaviour of small investors in the Hong Kong derivatives markets: A factor analysis - Tai-yuen Hon (Journal of Risk and Financial Management, 2012)
This paper investigates the behaviour of small investors in Hong Kong's derivatives markets. The study period covers the global economic crisis of 2011- 2012, and we focus on small investors' behaviour during and after the crisis. We attempt to identify and analyse the key factors that capture their behaviour in derivatives markets in Hong Kong. The data were collected from 524 respondents via a questionnaire survey. Exploratory factor analysis was employed to analyse the data, and some interesting findings were obtained. Our study enhances our understanding of behavioural finance in the setting of an Asian financial centre, namely Hong Kong.
Keywords: 330; Behavioural finance; factor analysis; small investors; derivatives markets